The semi-analytical motion theory of the third order in planetary masses for the Sun – Jupiter – Saturn – Uranus –Neptune's system. Issue Volume 15:Issue S364(2019) (October 2021) - Perminov, Alexander; Kuznetsov, Eduard
Abstract: The averaged four-planetary motion theory is constructed up to the third order in planetary masses. The equations of motion in averaged elements are numerically integrated for the Solar system's giant planets for different initial conditions. The comparison of obtained results with the direct numerical integration of Newtonian equations of motion shows an excellent agreement with them. It suggests that this motion theory is constructed correctly. So, we can use this theory to investigate the dynamical evolution of various extrasolar planetary systems with moderate orbital eccentricities and inclinations.